Health-related Quality of Life and Exercise Capacity in Double Lung Transplant Recipients With Baseline Lung Allograft Dysfunction - Alisha Rullay, BSc; Karina Kaur, BSc; Jennifer Holman, PT; Laura C. van den Bosch, MD; Justin G. Weinkauf, MD; Jayan Nagendran, MD, PhD; Rhea A. Varughese, MD; Alim S. Hirji, MD; Dale C. Lien, MD; Jason C. Weatherald, MD; Kieran M. Halloran, MD (Transplantation Direct)
Background. Baseline lung allograft dysfunction (BLAD) after lung transplant is associated with an increased risk of dying, but the association with health-related quality of life (HRQL) and exercise capacity is not known. We hypothesized that BLAD would be associated with reduced HRQL and 6-min walk distance (6MWD) at 1 y post–lung transplant. Methods. We analyzed patients who underwent lung transplants in our program from 2004 to 2018 who completed 1-y 36-item Short Form (SF-36) questionnaire and 6MWD testing. We secondarily analyzed the Beck Depression Inventory and Borg dyspnea scores in patients using the available data. We defined BLAD as a failure of both forced expiratory volume in 1 s and forced vital capacity to reach ≥80% predicted of a healthy reference population’s lung function on 2 consecutive tests ≥3 wk apart at any time point posttransplant. We tested the relationship between BLAD status and SF-36 physical component summaries and 6MWD using least squares regression, adjusting for age at transplant, sex at birth, and primary lung disease. Results. Two hundred sixty-four patients were included, 96 (36%) of whom met the criteria for BLAD. Patients with interstitial lung disease as an indication for transplant and those who received older, female, and heavy smoking donors were at increased risk of BLAD. SF-36 physical component summary scores were lower in patients with BLAD (75 versus 85; P = 0.0076), as were 6MWD values (528 versus 572 m; P = 0.0053). BLAD was associated with lower SF-36 scores (P = 0.0025) and 6MWD (P = 0.0008) in adjusted regression models at 1 y posttransplant. We did not observe differences in Beck Depression Inventory or Borg scores. Conclusions. BLAD was associated with reduced HRQL and 6MWD scores at 1 y posttransplant in adjusted models. This suggests that poor posttransplant lung function could contribute to lower HRQL and exercise capacity in lung recipients and is worthy of further exploration in terms of causes, prevention, and treatment.